Reservorios celulares del virus de inmunodeficiencia humana tipo 1 (VIH-1): características celulares y moleculares - Arcia Anaya, Eliuth David; Montoya Guarín, Carlos Julio; Rugeles López, María Teresa (Iatreia, 2014)
Human immunodeficiency virus type 1 (HIV-1) can establish a latent infection in different kinds of cells, which constitute the reservoirs for the virus and allow its maintenance in the body indefinitely. The main reservoirs of HIV-1 are resting CD4+ T cells, although other cells, among them monocytes/macrophages, and dendritic cells may also act as such. Different mechanisms contribute to the establishment and maintenance of latency in those cells, among them: transcriptional interference, low availability of transcription factors, chromatin condensation, and some microRNA that block viral translation. Knowledge of these mechanisms is crucial for the development of new drugs that may eliminate the virus from the body and lead to a cure.